Efficacy of the Renal-guard system in the prevention of contrast-induced nephropathy following cardiac interventions among patients with chronic kidney disease - Yasmin, Farah; Mashkoor, Yusra; Najeeb, Hala; Shaikh, Ayra Asim; Nusrat, Butool; Moeed, Abdul; Asghar, Muhammad Sohaib; Alraies, Chadi (Frontiers in Cardiovascular Medicine, 2025)
BackgroundContrast-induced nephropathy (CIN), also called as contrast associated-acute kidney injury (CA-AKI) is a common complication following cardiac procedures. KDIGO guidelines define CIN as a ≥25% increase in serum creatinine or an absolute increase of at least 0.5 mg/dl 48–72 h post-contrast administration. The single most effective measure in preventing CIN is peri-procedural intravascular hydration typically from 12 h before to 24 h after contrast media exposure but has limitations. Recently, the RenalGuard (RG) system has emerged as a new tool, demonstrating safer and more efficient hydration and reducing the incidence of AKI caused by CIN.AimsWe conducted this meta-analysis on the effectiveness of the RG system in preventing CIN in patients undergoing cardiac interventions.MethodsA comprehensive literature search of PubMed (MEDLINE), Science Direct, and Embase was conducted from its inception until February 2024 for randomized controlled trials (RCTs) including patients aged >18 years undergoing cardiac procedures with underlying chronic kidney disease (CKD), estimated glomerular filtration rate (eGFR) 20–60 ml/min/1.73 m2 and left ventricular ejection fraction (LVEF) >50%. The outcomes of interest were risk of CIN, risk of renal replacement therapy (RRT), in-hospital mortality and 30-day mortality, major adverse cardiovascular events (MACE), changes in serum creatinine (sCr) levels, and incidence of pulmonary edema. A random-effects meta-analysis was performed using Review Manager (RevMan) [Computer Program] Version 5.4 Cochrane Collaboration.ResultsA total of 9 RCTs including 3,215 patients with CKD undergoing cardiac procedures on volume expansion strategies were included with 1,802 patients on the RG system and 1,413 patients using alternate volume expansion techniques. Pooled analysis of 9 RCTs reported a significantly lower risk of CIN in patients using the RG system vs. control [OR 0.51 (0.35, 0.74), P = 0.0004; I2 = 55%]. There was no significant difference in the risks of RRT, in-hospital mortality, 30-day MACE, pulmonary edema, or change in sCr levels.ConclusionThis meta-analysis indicates the beneficial utilization of the RG system in populations with moderate-to-high risk and underlying CKD undergoing cardiac interventions in preventing CIN. However, it did not demonstrate a notable impact on mortality, RRT, MACE, pulmonary edema, and sCr levels when compared to the control group.